Дослідження та розробка оцінки якості послуг - Кулічко-Павленко, І. С. (ХНУРЕ, 2023)
The purpose of the work is to improve of the fitness center service level by developing elements of the company's quality system. The object of the study is the elements of the quality management system of an enterprise serving the population - a fitness center. A system of objects is proposed for quality management at the enterprise. Methods for assessing the quality of fitness center services have been developed. The characteristic of research solutions is given. The object of the study is the elements of the quality management system of an enterprise serving the population - a fitness center.